1983
DOI: 10.1111/j.1475-097x.1983.tb00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow‐volume relations in coronary circulation and distribution of coronary flow into nutritional and non‐nutritional compartments

Abstract: Simultaneous assessment of coronary flow and flow-volume relation makes it possible to evaluate the dilatatory responses of coronary vasculature. A new set up of methods for investigation of the coronary circulation was employed to study the nature of the coronary flow and volume responses to dipyridamole in dogs. The turnover rate of coronary blood, the reciprocal value of the mean transit time, can be accurately determined by computer simulation analysis of coronary dye dilution curves. After intravenous dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, because vessels are included in the myocardium compartment, one can argue that dipyridamole increases both myocardial blood flow and vascular volume by vasodilatation, and that the increased K, is related more to a volume increase than a flow effect. By comparing the mean transit-time of coronary blood with the coronary blood flow, Virtanen et al (23) deduced that no significant increase in the myocardium blood volume is induced by dipyridamole. With adenosine (a final effector of dipyridaniole), Cristal et al (24) found no change of the blood volume of small vessels with a diameter <loo pm, but did find a 35% increase of the total coronary blood volume (including the main coronary arteries).…”
Section: Effect Of Dipyridamolementioning
confidence: 99%
“…Moreover, because vessels are included in the myocardium compartment, one can argue that dipyridamole increases both myocardial blood flow and vascular volume by vasodilatation, and that the increased K, is related more to a volume increase than a flow effect. By comparing the mean transit-time of coronary blood with the coronary blood flow, Virtanen et al (23) deduced that no significant increase in the myocardium blood volume is induced by dipyridamole. With adenosine (a final effector of dipyridaniole), Cristal et al (24) found no change of the blood volume of small vessels with a diameter <loo pm, but did find a 35% increase of the total coronary blood volume (including the main coronary arteries).…”
Section: Effect Of Dipyridamolementioning
confidence: 99%